THE ROLE AND PLACE OF INFORMATION SECURITY IN THE OVERALL SYSTEM OF THE STATE'S NATIONAL SECURITY - Horulko, Vladyslav (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2022)
Introduction. The state's information policy is an important component of the state's foreign and domestic policy and includes all spheres of society. The rapid development of the information sphere causes the appearance of fundamentally new threats to the interests of the individual, society, the state and its national security. The fact that the information component is a stable object of manipulation in the conditions of hybrid war adds to the acuteness of the problem. Since the difficult political situation in which Ukraine has been in recent years, the continuous deterioration of the state's reputation on the international arena is caused by a number of factors, among which the inadequate state of the information security system is a significant factor. In Ukraine, there is an objective need for state-legal regulation of scientific, technical and information activities, which would correspond to the realities of the modern world and the level of development of information technologies, the norms of international law, but at the same time effectively protect Ukraine's own national interests.Short  list  of  main  results. Summary of main results. The article examines the issue of information security as a component of the state's national security. The information security of the state is defined by the degree of its protection and the stability of the main spheres of life in relation to dangerous, destabilizing and destructive informational influences affecting the interests of the state both at the level of implementation and extraction of information. Internal and external information threats to Ukraine's national security and ways to ensure the country's information security are identified. In today's conditions, the informational component of the state's national security plays an extremely important role due to the risks and threats present in it, which include cyberterrorism, cybercrime, aggressive propaganda, the spread of anti-constitutional and anti-state slogans, limiting public access to public information, etc.Attention is focused on the fact that the state information policy should reflect the urgent problems that have arisen in the information field. Effective implementation of strategic priorities, fundamental principles and tasks of the state policy of information security requires improvement of legal and organizational mechanisms of information security management.Conclusions. The article proposes to consider information security as a necessary component of the state's national security, as well as a global problem of information protection, information space, information state sovereignty and information support for state decision-making.KEY WORDS: national security, information security, state sovereignty, hybrid warfare, ensuring information security.